Investigating the Flipped English Learning Model at Islamic Junior Secondary School - St. Anisam; Nurdin Noni; Chairil Anwar Korompot (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study aims to investigate students' engagement in learning English using the flipped learning model at MTs. Yapit Tonrorita. The flipped learning model was chosen for its potential to increase students' preparedness and interactive activity during in-class time. Employing a qualitative research method with a descriptive approach, the study found that students generally exhibited positive engagement despite facing some obstacles. In terms of behavioral engagement, students showed good attention and cooperation, especially in group work; however, a gender gap was observed, with female students being more active in verbal discussions while male students remained passive. In conclusion, the Flipped Learning model effectively boosted students' behavioral and emotional engagement. The study implies the need for tailored instructional strategies within the flipped learning model to specifically address the observed gender gap in participation and mitigate student cognitive reliance on the teacher.